VARIABILITY OF ACCOUNTING POLICIES – ADVANTAGES AND DISADVANTAGES - Bojarenko, Julija (Copernican Journal of Finance & Accounting, 2018)
There are several provisions of accounting policy, which are not regulated by the legislation of the Republic of Latvia. As a result, companies are free to develop and adopt recognition criteria and the methods of evaluation and accounting for items of their financial statements. This article deals with the choice of recognition criteria and the methods of evaluation of and accounting for fixed assets. The aim of the article is to develop recommendations on how to resolve the issue of accounting policy variabilities for the companies of the Republic of Latvia. The objects of the study are recognition criteria and the methods of evaluation and accounting of fixed assets. The recommendations on the solution of the issues related to variability of fixed asset accounting policy are based on the determination of materiality criteria.